Comparison of CURB 65 and SCAP score in predicting outcome of CAP: A single center study - Sharma, Lucky; Pant, Subash; Neopane, Arpana (Journal of General Practice and Emergency Medicine of Nepal, 2018)
Introduction: Community acquired pneumonia is one of the leading cause of death. CURB-65 and SCAP score are tools to measure the severity of disease. CURB-65 uses relatively less variables than SCAP in scoring, this study is designed to measure the usefulness of both score in predicting outcome in our context. Method: This is descriptive, cross sectional quasi experimental study conducted in Kathmandu Medical College teaching hospital from July 2012 December 2012. Patient more than 18 years were scored and with CURB-65 and SCAP score and followed to see the outcome. Sensitivity and specificity was calculated. Both scores were compared for outcome using McNemer’s test. Result: Total 127 patient with mean age of 57 years were included. Total number of patient included in the study was 127 Mean age of patient was 57.66 years with two standard deviation of 19.46 years. Mortality rate was 5.5%. Male were 48(37.8%) and female were 79(62.2%). There was positive correlation with both CURB-65 (0.19, p=0.02) and SCAP (0.18, p=0.04) score on level of care required at hospital. There was no difference between CURB 65 and SCAP score in predicting outcome (p>0.05). Conclusion: There was no significant difference between predicting outcome with CURB-65 and SCAP score. Though CURB-65 uses less variables than SCAP score, it is equally effective in predicting the outcome or severity of disease.